2016
DOI: 10.5492/wjccm.v5.i4.228
|View full text |Cite
|
Sign up to set email alerts
|

Early debridement and delayed primary vascularized cover in forearm electrical burns: A prospective study

Abstract: AIMTo look into the management options of early debridement of the wound, followed by vascularized cover to bring in fresh blood supply to remaining tissue in electrical burns.METHODSA total of 16 consecutive patients sustaining full thickness forearm burns over a period of one year were included in the study group. Debridement was undertaken within 48 h in 13 patients. Three patients were taken for debridement after 48 h. Debridement was repeated within 2-4 d after daily wound assessment and need for further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Prevention of electrical injuries is still difficult in this group because of work-related risks. 12,13 The results of other studies showed the same results that the cause of electrical injury mainly occurred while working.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Prevention of electrical injuries is still difficult in this group because of work-related risks. 12,13 The results of other studies showed the same results that the cause of electrical injury mainly occurred while working.…”
Section: Discussionmentioning
confidence: 55%
“…The average age of patients with electric burns was 27.40 for men and 18.80 for women. 11 A study by Mene (2016) showed a total of 16 patients ranging from 10-45 years old, with the average age being 26 years old. 12,13 Another study showed that most patients aged 30-40 years old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The follow-up scan showed no new 'cold' areas and the measured non-tracer avid area showed no significant difference, thereby suggesting that extent of bone viability predicted in the pre-operative scan was accurate in all the cases. Previous studies have reported the efficacy of radionuclide scintigraphy for prediction of bone viability in electrical contact burns of limbs [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of objective tools used for assessing bone viability have shown limitations [9,10]. Radioisotope bone imaging has been successfully used as an objective tool for assessment of bone viability in electrical injuries [10,11]. This study was conducted to evaluate the role of 18 F Sodium Fluoride PET - Computed Tomography ( 18 F NaF PET-CT) in aiding the surgeon in anatomical localization of the extent and depth of dead and viable bone in electrical contact burns of the scalp.…”
Section: Introductionmentioning
confidence: 99%